THE S-CURVES DYNAMICS OF TRADE: The Case Study of Pakistan - Nabeela KOUSAR * (Pakistan Journal of Applied Economics, 2018)
The recent literature looks at correlation coefficients between the current exchange rate and the past and future values of trade balance. It is postulated that these coefficients are positive between the current exchange rate and the future trade balance values; but are negative between the current exchange rate and the past values of trade balance, resembling the S-curve pattern. For the first time this study, try to determine the existence of S-curve for aggregate trade and sixteen industries of Pakistan trading with the world. Industries representing the Scurve are less in number; hence, only the exchange rate depreciation is not a fruitful option to boost the trade balance.